2010
DOI: 10.1016/j.bmcl.2009.11.083
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted synthesis and in vitro cytotoxicities of substituted (Z)-2-amino-5-(1-benzyl-1H-indol-3-yl)methylene-1-methyl-1H-imidazol-4(5H)-ones against human tumor cell lines

Abstract: The synthesis of several novel substituted (Z)-2-amino-5-(1-benzyl-1H-indol-3-yl)methylene-1-methyl-1H-imidazol-4(5H)-ones structurally related to aplysinopsin have been carried out under microwave irradiation and conventional heating methods. The analogs 3a, 3b, 3d–3g, and 3k and 3l were evaluated for their in vitro cytotoxic activity against an NCI 60 human tumor cell line panel. Compound 3f exhibited good growth inhibitory properties against all but four of the human cancer cell lines examined, and afforded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…1), 1 and we have also described the radiosensitizing activity of some related N -benzylindole analogs ( B , Fig. 1) in parallel with their cytotoxic properties.…”
mentioning
confidence: 53%
“…1), 1 and we have also described the radiosensitizing activity of some related N -benzylindole analogs ( B , Fig. 1) in parallel with their cytotoxic properties.…”
mentioning
confidence: 53%
“…This synthesis has since been used to make a variety of analogues, 117,125 including 5,6-dibromo-2′-demethylaplysinopsin 126 and several series of N-alkylated aplysinopsin derivatives used for biological testing. [127][128][129] The conditions for this reaction vary but typically require heat and addition of a base, such as piperidine. A microwave-assisted method has been reported as well, where the reaction was microwaved for 30-60 seconds with creatinine and NaOAc.…”
Section: (4h)-imidazol-4-one Containing Natural Products and Their Total Synthesesmentioning
confidence: 99%
“…Structure B ). 8 In this respect, Li et al have synthesized and studied a series of structurally related N -heterocyclic indolyl glyoxylamides (Fig 1 . Structure C ), and found that such compounds possess marked activity against several cancer cell lines, including multidrug resistance (MDR) cell lines.…”
mentioning
confidence: 99%